Utility of CD4 count measurement in the era of universal antiretroviral therapy: an analysis of routine laboratory data in Botswana. Issue 1 (2nd September 2020) - Leeme, TB; Mine, M; Lechiile, K; Mulenga, F; Mosepele, M; Mphoyakgosi, T; Muthoga, C; Ngidi, J; Nkomo, B; Ramaabya, D; Tau, M; Tenforde, MW; et al.
Abstract : Objectives: National guidelines in Botswana recommend baseline CD4 count measurement and both CD4 and HIV viral load (VL) monitoring post‐antiretroviral therapy (ART) initiation. We evaluated the utility of CD4 count measurement in Botswana in the era of universal ART. Methods: CD4 and VL data were analysed for HIV‐infected adults undergoing CD4 count measurement in 2015–2017 at the Botswana Harvard HIV‐Reference Laboratory. We determined (1) the proportion of individuals with advanced HIV disease (CD4 count < 200 cells/µL) at initial CD4 assessment, (2) the proportion with an initial CD4 count ≥ 200 cells/µL experiencing a subsequent decline in CD4 count to < 200 cells/µL, and (3) the proportion of these immunologically failing individuals who had virological failure. Logistic regression modelling examined factors associated with advanced HIV disease. CD4 count trajectories were assessed using locally weighted scatterplot smoothing (LOWESS) regression. Results: Twenty‐five per cent (3571/14 423) of individuals with an initial CD4 assessment during the study period had advanced HIV disease at baseline. Older age [≥ 35 years; adjusted odds ratio (aOR) 1.9; 95% confidence interval (CI) 1.8–2.1] and male sex were associated with advanced HIV disease. Fifty per cent (7163/14 423) of individuals had at least two CD4 counts during the study period. Of those with an initial CD4 count ≥ 200 cells/µL, 4% (180/5061) experienced a decline in CD4 count to < 200 cells/µL; the majority of CD4 count declines were in virologically suppressed individuals and transient. Conclusions: One‐quarter of HIV‐positive individuals in Botswana still present with advanced HIV disease, highlighting the importance of baseline CD4 count measurement to identify this at‐risk population. Few with a baseline CD4 count ≥ 200 cells/µL experienced a drop below 200 cells/µL, suggesting limited utility for ongoing CD4 monitoring.